A Comparison of Colistin versus Colistin Plus Meropenem for the Treatment of Carbapenem-Resistant Acinetobacter baumannii in Critically Ill Patients: A Propensity Score-Matched Analysis - Wasan Katip; Suriyon Uitrakul; Peninnah Oberdorfer (MDPI AG, 2020)
Carbapenem-resistant Acinetobacter baumannii (CRAB), an important nosocomial pathogen, occurs particularly in the intensive care unit (ICU). Thus, the aim of this study was to compare the efficacy and safety of documented treatment with colistin monotherapy versus colistin plus meropenem in critically ill patients with CRAB infections at Chiang Mai University Hospital (CMUH). We conducted a retrospective cohort study of critically ill patients with CRAB infections in an ICU from 2015 to 2017, who received colistin monotherapy versus colistin plus meropenem. After propensity score matching, an adjusted odds ratio (aOR) of a 30-day mortality rate in patients who received colistin plus meropenem was 0.43 compared to those who received colistin monotherapy (95% CI, 0.23-0.82, p = 0.01). aORs of clinical response and microbiological response were also higher in patients who received colistin plus meropenem (1.81, 95% CI 1.01-3.26, p = 0.048 and 2.08, 95% CI 1.11-3.91, p = 0.023, respectively). There was no significant difference in nephrotoxicity (aOR, 0.76, 95% CI, 0.43-1.36, p = 0.363) between colistin monotherapy and colistin plus meropenem. In conclusion, the addition of meropenem to colistin caused a reduction in 30-day mortality, higher clinical and microbiological responses, and did not increase nephrotoxicity compared to colistin monotherapy. Furthermore, 30-day mortality was significantly related with age, receiving vasopressor, having malignancy, and the APACHE II score.